Pengelolaan Zakat, Infaq dan Sedekah dalam Pengembangan Usaha Mikro di Baznas Gresik - Mariroh, Silvi Mata'atul; Anwar, Moch Khoirul (Universitas Negeri Surabaya, 2020)
Poverty illustrates a multidimensional problem on economic factors, the emergence of programs implemented by the government to reduce the number of poor people such as distributing cash donations. Therefore the plan to make it happen Gresik Regency Baznas prepares a work program that is